Distinctive exotic flavour and aroma compounds of some exotic tropical fruits and berries: A review. - Olusegun, Lasekan; Ali Abbas, Kassim (Taylor & Francis, 2012)
The characteristic flavor of exotic tropical fruits is one of their most attractive attributes to consumers. In this article, the enormous diversity of exotic fruit flavors is reviewed. Classifying some of the exotic fruits into two classes on the basis of whether esters or terpenes predominate in the aroma was also attempted. Indeed, as far as exotic tropical fruits are concerned, the majority of fruits have terpenes predominating in their aroma profile. Some of the fruits in this group are the Amazonian fruits such as pitanga, umbu-caja, camu-camu, garcinia, and bacuri. The ester group is made up of rambutan, durians, star fruit, snake fruit, acerola, tamarind, sapodilla, genipap, soursop, cashew, melon, jackfruit, and cupuacu respectively. Also, the role of sulphur-volatiles in some of the exotic fruits is detailed.